Multiuser detection for continuous phase CDMA - Müller, Ralf (2011 1st IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, APWC'11, 2011)
This paper studies linear multiuser detection for code-division multiple-access (CDMA) with continuous-time constant envelope and continuous phase. The restriction to continuous phase is found to cause negligible degradation of multiuser efficiency when detected by means of linear multiuser detectors. This holds for both classical linear multiuser detection as well as for multistage detection based on universal weight design. © 2011 IEEE.
Keywords: Multiaccess communication; Signal to noise Ratio; Bandwidth; Interference; Multiuser detection; Detectors; Degradation